Criminal activity in Ukraine in the light of current conditions - Аркуша, Лариса Ігорівна; Аркуша, Л. І.; Аркуша, Лариса Игоревна; Arkusha, Larysa I.; Корнієнко, Максим Вікторович; Корнієнко, М. В.; Корниенко, Максим Викторович; Korniienko, Maksym V.; Берендєєва, Анастасія Ігорівна; Берендєєва, А. І.; Берендеева, Анастасия Игоревна; Berendieieva, Anastasiia I. (Editorial Primmate S. A. S., 2019)
In this paper, the authors expressed their own vision of the peculiarities, trends and interdependence of the criminal activity related in Ukraine nowadays. The present analysis focuses on investigating and analyzing the prospect, scope and peculiarities of criminal acts in modern Ukraine. The typification of signs of criminal activity in Ukraine gives the authors free rein to argue that nearly all types of this criminal activity have corruption orientation, either directly or indirectly. The results of using content analysis method made it possible to claim that corrupt practices occur in all sectors of the population from an economic and social basis to legal, cultural, spiritual and ideological strata of society and may affect special conditions as a source of revenue. Moreover, the authors used methods of formal logic (analysis, synthesis, deduction, induction, analogy), method of system analysis, as well as a statistical method. Forensic analysis of the manifestations of criminal activity in Ukraine, makes it possible to draw the following conclusions: criminal activity in Ukraine is inextricably linked and interdependent with political processes taking place both in Ukraine and in temporarily uncontrolled territories. In fact, all its manifestations are directly or indirectly political in nature, even if we analyze crimes committed individually, they are not only aimed at achieving a self-serving purpose for their own benefit, but may also be caused by a radical (sometimes emotional) attitude towards socio-political processes. There are also signs of mutually beneficial relations between criminal organizations and authorities in Ukraine, so the research helps to predict the replacement of the norms of law and morality due to the ideology of the criminal activity in some strata of society that may become more acceptable for them.

У даній роботі автори висловили власне бачення особливостей, тенденцій та взаємозалежності специфіки злочинної діяльності від сучасних особливих умов.Проведений аналіз зосереджується на дослідженні та оцінці перспективи, обсягу та особливостей злочинних діянь в Україні. Типізуючи прояви злочинної діяльності, з урахуванням сучасних умов, автори доводять, що фактично всі її прояви безпосередньо або побічно залежать від корупційних злочинів.Результати використання методу контент-аналізу дали змогу стверджувати, що корупція виявлена у всіх верствах населення незалежно від економічного та соціального рівня, а також правових, культурних, духовних та ідеологічних переконань. Більш того, автори використали методи формальної логіки (аналізу, синтезу, дедукції, індукції, аналогії), метод системного аналізу, а також статистичний метод. Аналіз сучасних проявів злочинної діяльності в Україні, дає можливість зробити такі висновки: злочинна діяльність в Україні, нерозривно пов’язана та взаємозалежна від політичних процесів, які відбуваються на території України. Фактично всі її прояви безпосередньо або побічно мають політичне забарвлення, навіть якщо ми аналізуємо злочини, які вчиняються одноособово, то вони спрямовані не тільки на досягання корисливої мети задлявласної вигоди, а можуть бути обумовлені і радикальним (інколи емоційним) ставленням до соціально-політичних процесів. Також спостерігаються ознаки взаємовигідних відносин між злочинними організаціями та владними установами в Україні, що дає можливість прогнозувати підміну окремою частиною верств населення норм моралі та права ідеологією злочинної діяльності, яка може стати для них більш прийнятною.
Arkusha L. Criminal activity in Ukraine in the light of current conditions / L. Arkusha, M. Korniienko, A. Berendieieva // Amazonia Investiga. – Vol. 8. - Issue 24. – Editorial Primmate S. A. S., 2019. – P. 386-391.
Keywords: crime; criminal activity; current conditions; special conditions; corruption; organized crime groups; злочинність; злочинна діяльність; сучасні умови; особливі умови; корупція; організовані злочинні групи; Research Subject Categories::LAW/JURISPRUDENCE